The issuance of warrants in rights offerings: Agency costs and signaling effects. (November 2017) - Balachandran, Balasingham; Kanapathippillai, Sutharson; Krishnamurti, Chandrasekhar; Theobald, Michael; Velayutham, Eswaran
We examine the issuance choice across rights issues of equity, unit offerings, and standalone warrants and investigate the market reactions to these issue types. We find that agency costs, growth opportunities, and current funding needs relative to assets in place are prime drivers of the type of equity issuance choice. Managers use quality signals such as underpricing, underwriting status, and the proportion of funds raised by exercising warrants in determining the features of the warrant issue. Furthermore, we document that the market reacts more favorably to standalone warrants issues than units and equity during the rights offering period.